2022
DOI: 10.1177/09603271221145422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thymoquinone on pharmacokinetics of 5-fluorouracil in rats and its effect on human cell line in vitro

Abstract: Thymoquinone (TQ) is one of the components extracted from Nigella sativa seeds and has antioxidant, anti-inflammatory, and anticancer effects. We evaluated the effect of TQ on 5-fluorouracil (5-FU) pharmacokinetics (PK) in vivo and in vitro on human colorectal cancer cell line. Ten Adult male Wistar rats were assigned to two groups. TQ treated group received intraperitoneal TQ once daily for 14 consecutive days (5 mg/kg). Both groups received intraperitoneal 5-FU (50 mg/kg) on day 15 and blood samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In this investigation, the MTT assay was employed, It was performed as it is one of the dependable techniques for evaluating cellular viability. Furthermore, it is renowned for its discerning detection of cellular proliferation, as it quantifies the rate of cellular growth through the utilization of a linear correlation between cellular activity and absorbance [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, the MTT assay was employed, It was performed as it is one of the dependable techniques for evaluating cellular viability. Furthermore, it is renowned for its discerning detection of cellular proliferation, as it quantifies the rate of cellular growth through the utilization of a linear correlation between cellular activity and absorbance [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination was found to decrease the expression of protumor genes, such as WNT, β-catenin, NF-κB, COX-2, inducible nitric oxide synthase (iNOS), VEGF, and increase the expression of antitumor genes, namely dickkopf-1 (DKK-1), cyclin dependent kinase inhibitor 1A (CDNK-1A), TGF-β1, TGF-βRII, Smad4 and glutathione peroxidase (GPx) [135]. Eftekhar and colleagues [136] reported similar findings. They showed that co-exposure of HT-29 cells to 5-FU and TQ resulted in greater cell inhibition than when the substances were used alone.…”
Section: Simultaneous Stimulation With Thymoquinone and Known Chemoth...mentioning
confidence: 99%
“…They showed that co-exposure of HT-29 cells to 5-FU and TQ resulted in greater cell inhibition than when the substances were used alone. They also showed that TQ has a synergistic effect on the pharmacokinetics of 5-FU [136]. TQ's effect on CRC and cancer stem cells, considered the most resistant to 5-FU, has also been studied.…”
Section: Simultaneous Stimulation With Thymoquinone and Known Chemoth...mentioning
confidence: 99%
“…Notably, the combined administration of TQ and 5-FU resulted in an enhanced cytotoxic effect compared to the individual suppressive impact of 5-FU. This combination demonstrated a significant suppressive effect at 5-FU concentrations of 0.027 and 0.055 mM, suggesting that TQ could potentially amplify the growth-suppressive effects of 5-FU on cancer cells [ 127 ]. The concurrent administration of 30 μM imatinib, a tyrosine kinase inhibitor, and 10 μM TQ resulted in the suppression of ABCB1, ABCG2, and hOCT1, thereby enhancing the uptake of imatinib in HCT-116 cells [ 128 ].…”
Section: Tq and Colorectal Cancermentioning
confidence: 99%